THE EFFECT OF LOAN ACCESSIBILITY AND FINANCIAL PLANNING ON ONLINE LOAN CONSUMER BEHAVIOR - Afrian Andika Yumna; Nur Ahmadi Bi Rahmani; Nursantri Yanti (Nurul Jadid University, 2025)
The purpose of this study is to ascertain how State Islamic University of North Sumatra (UINSU) Faculty of Economics and Islamic Business (FEBI) students use online loan services in connection to loan accessibility and financial planning. The background of this study is the rise in student use of online loan services, which are typically used to finance lifestyle needs rather than necessities. Through purposive sampling, 100 students were chosen to take part in the survey for this associative quantitative study. SPSS version 25 and multiple linear regression were used for data analysis. Purposive sampling was used to select 100 students for this study, which employs an associative approach and survey method. A p-value of 0.000 and a regression coefficient of 0.638 demonstrate that loan accessibility has a significant and positive impact on consumer behavior. A regression coefficient of 0.438 and a p-value of 0.000 show that financial planning has a significant and advantageous effect. Both variables have a significant impact on consumer behavior, as evidenced by the significance value of 0.000 and the F-count value of 93.419 (which is higher than the F-table value of 3.09), respectively. With a coefficient of determination (R2) of 0.658, financial planning and loan accessibility account for 65.8% of the variation in student consumption patterns. The remaining 34.2% are affected by factors that are not part of the research model